Genome-wide identification, characterization, and expression analysis of the TRAF gene family in Chinese tongue sole (Cynoglossus semilaevis). Issue 96 (January 2020) - Li, Kun-ming; Li, Ming; Wang, Na; Chen, Ya-dong; Xu, Xi-wen; Xu, Wen-teng; Wang, Lei; Chen, Song-lin
Abstract: Tumor necrosis factor (TNF) receptor-associated factors (TRAFs) play crucial roles as signaling mediators for the TNF receptor (TNFR) superfamily and the interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) superfamily. TRAFs collectively play important roles in multiple biological processes and organismal immunity. However, systematic identification of the TRAF gene family in teleost fish has not yet been reported, and there is little available information about its roles in innate immunity in Chinese tongue sole ( Cynoglossus semilaevis ), an aquaculture fish of high economic value. In the present study, we identified and characterized seven TRAF genes, namely, CsTRAF2a, CsTRAF2b, CsTRAF3, CsTRAF4, CsTRAF5, CsTRAF6 and CsTRAF7, in Chinese tongue sole, and the complete ORFs of the CsTRAFs were cloned. Sequence analysis revealed various genomic structures of the CsTRAFs and showed that they contain typical conserved domains compared with mammalian TRAFs. Phylogenetic analysis indicated the evolutionary relationships of TRAF family members in teleost fish and revealed an absence of TRAF1 in most species and TRAF5 in some species of teleosts. Analysis of the gene structures and motifs showed the diversity and distribution of exon-intron structures and conserved motifs in Chinese tongue sole and several other teleost species. Real-time quantitative PCR was used to investigate the expression patterns of CsTRAF genes in tissues of healthy fish and in the gills, livers and spleens of fish after bacterial infection with Vibrio harveyi . The results indicate that only CsTRAF2a is relatively highly expressed in the brain and that the other CsTRAFs are highly expressed in immune-related tissues and may participate in the immune response after infection with pathogenic bacteria. Functional analysis of CsTRAF3, CsTRAF4 and CsTRAF6 revealed that only CsTRAF6 could strongly activate the NF-кB pathway after overexpression of CsTRAF3, CsTRAF4 and CsTRAF6 in HEK-293T cells. This systematic analysis provided valuable information about the diverse roles of TRAFs in the innate immune response to pathogenic bacterial infection in teleost fish and will contribute to the functional characterization of CsTRAF genes in further research. Highlights: We identified seven TRAF genes in Chinese tongue sole, subsequently cloned the complete ORFs of CsTRAFs. Bioinformatic analysis confirmed the identities and nomenclature. The CsTRAFs are highly expressed in immune-related tissues and participate in the immune response after V. harveyi infection. Only CsTRAF6 could strongly activated NF-кB pathway after co-transfection with NF-кB reporter plasmid in HEK-293T cells.